The relationship between innovation attributes and the willingness to use ICT innovations among employees: a case study at Perkeso in Kuching, Sarawak / Muhammad Faiz Mohammad Taufik - Mohammad Taufik, Muhammad Faiz (2016)
The purposes of this study were to find out the most significant types of innovation attributes of the employees in order to increase the willingness to use ICT innovations and to determine the relationship between innovation attributes and the willingness to use ICT innovations among employees at PERKESO in Kuching, Sarawak. This study used the census method to do the study on the entire population at PERKESO in Kuching, Sarawak. The empirical data had been collected using the questionnaire which was divided into three sections. Section A focused on the demographic background of the respondents, Section B focused on the types of innovation attributes (relative advantage and complexity) and Section C focused on the willingness to use ICT. A set of 50 questionnaires were distributed to 50 respondents at PERKESO in Kuching, Sarawak with an 88% response rate. The data was analyzed using the SPSS Version 20. Based on the findings of this study, it can be concluded that relative advantage and complexity were the most significant types of innovation attributes at PERKESO in Kuching, Sarawak. This study highlighted that there was a positive very strong relationship between innovation attributes and the willingness to use ICT innovations at PERKESO in Kuching, Sarawak.